Clinicopathological Significance of Mucin 2 Immunohistochemical Expression in Colorectal Cancer: A Meta-Analysis - Li, Li; Huang, Pei-lin; Yu, Xiao-jin; Bu, Xiao-dong (Chinese Journal of Cancer Research; Vol 24, No 3 (September 01, 2012): Chinese Journal of Cancer Research, 2012)
Objective: To evaluate the association between mucin 2 (MUC2) expression and clinicopathological characters of colorectal cancer. Methods: A literature search was performed on December 31, 2010 according to defined selection criteria. We evaluated the correlation between MUC2 (detected by immunohistochemistry) and clinicopathological characters of colorectal cancer. According to the tumor histological type, differentiation, location and TNM staging of colorectal carcinoma, we divided the clinicopathological characteristics into different subgroups. Fixed and random effects models were applied for estimation of the summarized risk ratios (RRs) and 95% confidence intervals (CIs) in different subgroups. Finally, forest plots and funnel plots were created to allow for visual comparison of the results or the effect of publication bias. Results: According with the inclusive criteria, fourteen studies (n=1,558) were eligible for the meta-analysis. We observed a trend towards a correlation of MUC2 higher positivity in mucinous than non-mucinous carcinoma (RR, 2.10; 95% CI, 1.30–3.40; P=0.002) and less positivity in distal than proximal colon (RR, 0.74; 95% CI, 0.64–0.85; P=0.000). There was no statistically significance for the association between MUC2 expression and differentiation or TNM staging of colorectal cancer, but MUC2 overexpression tended to be associated with the presence of T stage tumor (RR, 1.17; P=0.052). Conclusion: MUC2 overexpression was associated with the mucinous and proximal colorectal cancer.